2017
DOI: 10.1111/jpn.12801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Royal Jelly on behavioural patterns, feather quality, egg quality and some haematological parameters in laying hens at the late stage of production

M. S. El‐Tarabany

Abstract: The aim was to elucidate the impact of Royal Jelly (RJ) on behavioural patterns, feather cover, egg quality and some blood haematological indices in laying hens (58-64 weeks of age). A total of 108 Tetra Brown laying hens were used in the current trial. The birds were divided into three equal groups (36 birds each). The pure RJ was prepared for immediate injection subcutaneously, as follows: the first treated group (RJ :100 mg/kg); the second treated group (RJ :200 mg/kg); the control group. The eating and dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In the current experiment, a significant increase of the erythrocyte counts in the RJ-treated groups indicated that RJ may have a stimulatory action on the erythrocytes synthesis and proliferation in the bone marrow. Our findings were harmonious with that reported by El-Tarabany [42] . Royal jelly had a protective role against many drugs [43] .…”
Section: Discussionsupporting
confidence: 93%
“…In the current experiment, a significant increase of the erythrocyte counts in the RJ-treated groups indicated that RJ may have a stimulatory action on the erythrocytes synthesis and proliferation in the bone marrow. Our findings were harmonious with that reported by El-Tarabany [42] . Royal jelly had a protective role against many drugs [43] .…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, RJ in ovo injection has been concluded to improve chick body weight [21], internal organ weight and luteinizing hormone (LH) and follicle-stimulating hormone (FSH) secretion without adverse effects on hatchability [22]. Furthermore, in ovo injection of RJ has been found to promote feed intake in broiler chicks with no effect on immunity against Newcastle disease virus (NDV) [23], egg quality parameters or erythrocyte counts [24].…”
Section: Introductionmentioning
confidence: 99%
“…According to Saeed et al [9], supplementing poultry diets with royal jelly provides an opportunity to maximize profits from safe and high-quality poultry products. Previous studies that have focused on supplementation of poultry diets with royal jelly (50-200 mg/kg) have shown a substantial increase in body weight, egg production, semen quality, and immune response, as well as producing healthier products [9,[83][84][85]. Under heat stress, administering royal jelly to growing rabbits can improve body weight gain and feed conversion ratio as well as alleviate the physiological stress caused by heat stress, according to [86].…”
Section: Royal Jellymentioning
confidence: 99%